Pengaruh E-Service Quality dan E-Trust terhadap E-Loyalty dengan E-Satisfaction sebagai Variabel Intervening pada Aplikasi Belanja Online Shopee: - Afik Melawati; Henny Welsa; Bernadetta Diansepti Maharani (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine whether there is an effect of e-service quality, e-trust, on e-loyalty: e-satisfaction as an intervening variable in the online shopping application, Shopee. The population used in this study are consumers or product buyers from the online shopping application Shopee in the city of Yogyakarta. This study uses a type of questionnaire that uses the Google form as a research tool. The research method used is purposive sampling technique. The sample used was 126 respondents. The data obtained from the questionnaire were then processed and analyzed using Multiple Linear Regression analysis with model accuracy (classical assumption test), hypothesis testing using the partial test (t) and determination test (R2) using the SPSS 25 program. The results in this study indicate that the variable e-service quality has a positive and significant effect on e-satisfaction, e-trust has a positive and significant effect on e-satisfaction, e-service quality has no positive and significant effect on e-loyalty, e-trust has no positive and significant effect on e-loyalty, e-satisfaction has a positive effect on e-loyalty, e-satisfaction has a positive and significant effect as an intervening variable the effect of e-service quality on e-loyalty, and e-satisfaction has a positive and significant effect as an intervening variable the effect of e-trust on e-loyalty . Keyword: e-service quality, e-trust, e-loyalty, e-satisfaction